THE EFFECT OF WATCHING ENGLISH MOVIE TO IMPROVE STUDENTS’ LISTENING SKILL - Maydina Putri; Juwita Boneka Sinaga (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
The objective of the study was to find out whether significant effect of watching English movie to improve students’ listening skill at SMAN 16 Batam in academic 2019/2020. The researcher used quantitative method and focused on quasi experimental. The population in this research is all of tenth grade students that consisted of 400 students that selected by using simple random sampling technique. The subject of the study was grade X social 1 and X4. The researcher conducted research in two classes as experimental class and control class. The researcher use quantitative data by giving pre-test and post-test measure the students’ listening skill. The result of the calculating t-test was tcount ttable (3,269 1,990). It means that Null hypothesis was rejected and alternative hypothesis was accepted. Therefore, in this research was a significant effect of watching English movie to improve students’ listening skill at tenth grade of SMAN 16 Batam. Moreover, watching English movie was gave positive effect to improve students’ listening skill. Watching English movie could motivate the students and interested in learning listening skill. Therefore, the English teacher could carry out the watching English movie to improve students’ listening skill.